Gambaran Pengetahuan Ibu Balita Stunting Tentang Sanitasi Air Bersih Di Wilayah Kerja Puskesmas Paruga Kota Bima Tahun 2024 - Putri Yayu; Nur Aidah; Nurbaety; Nur Islamyati (2025)
Clean water sanitation is a crucial aspect of human life. Contaminated water sources can be a contributing factor to stunting, as water tainted with bacteria can cause diseases such as diarrhea and pneumonia, which subsequently affect a child's nutritional status, leading to malnutrition, stunting, undernourishment, and wasting. Clean water sanitation, particularly the use of protected versus unprotected water sources, significantly influences the incidence of stunting. While improved knowledge of Water, Sanitation, and Hygiene (WASH) is fundamental for better individual and public health, as well as sustainable community development, having good knowledge does not necessarily guarantee positive attitudes and practices. Data from the Paruga Community Health Center in Bima City shows fluctuating stunting cases: 194 cases in 2021, which decreased to 105 cases in 2022, and increased again to 126 cases in 2023. This study aims to describe the knowledge of mothers with stunted toddlers regarding clean water sanitation in the working area of the Paruga Community Health Center, Bima City, in 2024. This research employs a quantitative descriptive method. The population consisted of 126 mothers of stunted toddlers. A sample of 31 respondents was selected using simple random sampling. Data were analyzed using univariate analysis. The findings indicate that the knowledge of mothers with stunted toddlers about clean water is generally poor, which is associated with the stunted nutritional status of their children.